Smallholder Forestry in the Western Amazon: Outcomes from Forest Reforms and Emerging Policy Perspectives - Pacheco, P.; Mejía, E.; Cano-Cardona, W.; Jong, W. de (MDPI, 2016)
The forest reforms unfolding during the last two decades in the western Amazon have embraced policy regimes founded on the principles of sustainable forest management. The policy frameworks adopted for smallholder forestry aimed to clarify forest rights including those of the indigenous people and smallholders, support the adoption of sustainable forest management and put a system in place to assure a legal timber supply. The emerging forest policy regimes have significantly shaped who has access to the forest, how the forest resources are used and the benefits that are utilized. We argue that forest reforms have not addressed some critical constraints facing smallholders in managing their forests either individually or collectively. Informal timber extraction persists with contradictory effects on smallholders and forests. Local participants continue to make a significant contribution in meeting a growing demand for timber through vigorous market networks that combine legal and illegal sources of timber supply. Some recent changes to forest policy frameworks emphasize approaches towards additional integrated forest management, simplification of regulations and incentives for improved forest management. We critically reflect on the scope, implementation and expected outcomes of these policy frameworks.